Pengaruh Gaya Kepemimpinan Kepala Ruangan terhadap Kinerja Perawat Pelaksana di Ruang Rawat Inap RSUD dr. Slamet Garut - Andhika Lungguh Perceka (Jurnal Medika Cendikia, 2018)
Nurses as one health worker plays an important role in efforts to achieve health development. In achieving good service quality the head of the room provides an important role in managing nursing care. The role of the head of the room as a manager is able to plan all activities undertaken by nurses, making the division of labor, provide direction of work, supervision and evaluation work. This is influenced by the leadership style of the head of the room in leading its members so that the goals of the organization can be achieved. This research method using descriptive correlation with cross sectional approach. The variables consist of the headroom leadership style and the performance of the implementing nurse. The population of all inpatient nurses was 296 people. Sampling method that is by using propotional stratified random sampling with obtained sample counted 74 people. The result of the research shows that leadership style of head of majority room with democratic leadership style is 42 people (56.8%). Performance of nurse executor of majority performing less good as many as 39 people (52.7%). Bivariate analysis using chi square. The results showed (p value = 0.731). conclusion: there is no correlation between leadership style of head of room to performance of nurse executor in General Hospital dr. Slamet Garut.